Removal of Reactive Dyes from Aqueous Solution by Adsorption on Coconut Coir Activated Carbon - Rashidah bt. Othman, Rashidah (2009)
The removal efficiency of two highly used reactive dyes (C. I. Reactive Red 180 and C. I. Reactive Blue 19) in aqueous solution by activated carbon prepared from coconut coir was investigated. Physicochemical characteristics of the coconut coir activated carbon were measured by ash content and pH.